Degradasi bahan organik di beberapa perkebunan teh di Jawa Barat - Restu Wulansari; Eko Pranoto (Jurnal Penelitian Teh dan Kina, 2018)
The tea production and the quality were over the years, especially in West Java, Indonesia. This had been affected by several factors including the aged of tea plantations, declining soil fertility, and soil degradation among other factors. Andisol is the most suitable soil and dominant in Indonesia for tea plantation. The objectives of this study were to evaluate the impact of long-term tea cultivation on soil organic matter degradation in 6 years (2011 and 2017) in tea plantations in Bandung, Bogor, Cianjur and Garut, West Java. Data analysis used the independent sample t-test with SPSS 16.0 at a significant level of 95%. This study used a quantitative descriptive method by comparing the levels of organic matter and macronutrients from 89 samples taken in 2011 and 2017. Soil samples were taken at a depth of 35-40 cm with a distance of 25cm of the tea plant. Conclusion of the study, that the levels of organic matter in the regions of Bandung, Cianjur, and Garut are not significantly different between 2011 and 2017; while in the Bogor area the level of organic matter in 2011 was 5.41% and decreased in 2017 was 4.40% (a decrease of 18.72%). However, based on C-organic data in 2011 and 2017 nutrient degradation has occurred in all locations. Decreasing organic matter can cause a low decrease in soil fertility and productivity of tea crops. Provision of organic matter and proper fertilization must be done to maintain soil fertility and productivity of tea plants.